Evaluation of Neutrophil-Lymphocyte Ratio and Platelet-Lymphocyte Ratio in Diabetic Kidney Disease Patients: A Hospital-Based Cross-Sectional Analysis - I Made Satya Pramana Jaya; Lydia Tantoso (Masters Program in Public Health, Sebelas Maret University, 2026)
Background: Diabetes mellitus represents a chronic metabolic disorder with globally increasing prevalence and is one of the leading causes of microvascular complications such as diabetic kidney disease (DKD). Chronic inflammation plays a crucial role in DKD pathogenesis, prompting exploration of simple inflammatory markers such as neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR). This study aimed to determine the relationship between NLR and PLR values with the incidence of DKD. Subject and Methods: This cross-sectional study employed consecutive non-random sampling technique. The study population consisted of all patients visiting Cinta Kasih Tzu Chi Cengkareng Hospital from January to April 2025, totaling 128 respondents. Secondary data from medical records were analyzed using Chi-Square test to determine associations between NLR and PLR (categorized as high vs low) with diabetic kidney disease incidence. Statistical analysis employed Chi-Square test with significance set at p<0.050. Results: Among 128 respondents, 64 (50.00%) were diagnosed with diabetic kidney disease. High NLR group comprised 101 respondents (78.90%), with 50 (39.10%) having DKD. High PLR group totaled 32 respondents (25.00%), with 19 (14.80%) having DKD. NLR demonstrated no significant association with DKD incidence (PR= 0.96; CI95% 0.48 to 1.41; p=0.828). PLR also showed no significant association with DKD incidence (PR= 0.89; CI95% 0.52 to 1.53; p=0.552). Conclusion: Neither NLR nor PLR demonstrates a significant relationship with diabetic kidney disease incidence at Cinta Kasih Tzu Chi Cengkareng Hospital. These findings suggest that NLR and PLR cannot be used as standalone predictors for DKD and should be considered alongside other clinical parameters in comprehensive diabetes management protocols.